High‐pressure sprayed siRNAs influence the efficiency but not the profile of transitive silencing. (19th January 2022) - Uslu, Veli Vural; Dalakouras, Athanasios; Steffens, Victor A.; Krczal, Gabi; Wassenegger, Michael
SUMMARY: In plants, small interfering RNAs (siRNAs) are a quintessential class of RNA interference (RNAi)‐inducing molecules produced by the endonucleolytic cleavage of double‐stranded RNAs (dsRNAs). In order to ensure robust RNAi, siRNAs are amplified through a positive feedback mechanism called transitivity. Transitivity relies on RNA‐DIRECTED RNA POLYMERASE 6 (RDR6)‐mediated dsRNA synthesis using siRNA‐targeted RNA. The newly synthesized dsRNA is subsequently cleaved into secondary siRNAs by DICER‐LIKE (DCL) endonucleases. Just like primary siRNAs, secondary siRNAs are also loaded into ARGONAUTE proteins (AGOs) to form an RNA‐induced silencing complex reinforcing the cleavage of the target RNA. Although the molecular players underlying transitivity are well established, the mode of action of transitivity remains elusive. In this study, we investigated the influence of primary target sites on transgene silencing and transitivity using the green fluorescent protein (GFP)‐expressing Nicotiana benthamiana 16C line, high‐pressure spraying protocol, and synthetic 22‐nucleotide (nt) long siRNAs. We found that the 22‐nt siRNA targeting the 3ʹ of the GFP transgene was less efficient in inducing silencing when compared with the siRNAs targeting the 5ʹ and middle region of the GFP. Moreover, sRNA sequencing of locally silenced leaves showed that the amount but not the profile of secondary RNAs is shaped by the occupancy of the primary siRNA triggers on the target RNA. Our findings suggest that RDR6‐mediated dsRNA synthesis is not primed by primary siRNAs and that dsRNA synthesis appears to be generally initiated at the 3ʹ‐end of the target RNA. Significance Statement: This work answers a long‐standing question about the role of siRNA triggers in initiating transitive silencing. By using high‐pressure spraying‐mediated delivery of synthetic siRNAs, we provided experimental evidence that the target position of 22‐nt‐long primary siRNAs influences the efficiency of RDR6‐driven dsRNA synthesis, but it does not change the profile of accumulating secondary siRNAs originating from processing of RDR6‐produced dsRNA.